KEY ASPECTS OF DIGITALIZATION IN MEDICAL TOURISM - Gulnara Karimovna Khudaykulova (Modern American Journals, 2025)
Medical tourism is becoming an important economic sector for Central Asian countries, including Uzbekistan. Digitalization plays a key role in improving the efficiency, transparency, and accessibility of medical services. This article examines electronic health records (EHRs), integrated digital platforms, and international experience, as well as prospects for their implementation in the region.
Keywords: Medical tourism, digitalization, electronic health records, integrated platforms, Uzbekistan, Central Asia.